Analysis of Mathematical Reasoning Ability Based on Problem Based Learning Value Comparison Material - Sipakkar, Tari Rodearna Br; Anim, Anim (Holistic Science, 2024)
Mathematical reasoning ability is a very important aspect in learning mathematics. This ability is a high-level ability that involves imagination and curiosity to think logically. Mathematical reasoning can be sharpened using the Problem Based Learning learning model, so this research was conducted to analyze the mathematical reasoning abilities of students at SMP Negeri 5 Kisaran using a qualitative descriptive approach. The subjects in this research were 32 students. The data used is written test results and observation results during the learning process which will then be analyzed using qualitative descriptive data analysis techniques including data reduction, data display and verification. The results of this research show that the mathematical reasoning ability of students in the high category is 8 people, 16 people are medium and 8 people are low, and the average value of the results of observations of mathematics learning activities in comparative material is 16.28125 with a percentage of 66.5%. which is included in the medium category. These results indicate that the reasoning abilities of students at SMP Negeri 5 Kisaran are in the medium category.